Pengaruh Pengalaman Pengguna Digital dan Personal Branding terhadap Minat Berwirausaha di E-Commerce pada Generasi Z - Febi Ardhani; Indra Hastuti; Khabib Alia Akhmad (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research aims to analyze the influence of digital user experience, personal branding, and trust on Generation Z's interest in e-commerce entrepreneurship. This quantitative study distributed questionnaires to Generation Z respondents who are active in e-commerce in the metropolitan area of Solo. Multiple linear regression analysis was used with a sample size of 100 respondents. The research findings are expected to contribute theoretically and practically to understanding the factors influencing entrepreneurial interest in the digital era, especially among Generation Z. The research concludes that: (1) digital user experience has a positive influence on Generation Z's interest in e-commerce entrepreneurship; (2) personal branding has a positive influence on entrepreneurial interest in e-commerce among Generation Z; (3) digital user experience, personal branding, and trust have a simultaneous influence on entrepreneurial interest in e-commerce among Generation Z.